'Recycle versus buy' scenarios in manufacturing strategy decisions: an empirical study. (11th August 2020) - Wilson, Shellyanne
This paper examines the 'recycle versus buy' decision-making process, which is becoming a critical decision area for companies operating in the plastics, paper, rubber and metal industries. Via the use of scenario analysis, applied in an in-depth case study that uses plastic buckets for packaging, decision alternatives and uncertainties are considered. The scenario analysis produced nested scenario logics, comprising four bases: volume of used-material collected; cost of used-material collection; cost of virgin material; and performance of new product made with high/low ratio of virgin material to recycled material, resulting in 16 possible scenario combinations. For each combination, market, technical and financial feasibility are examined. For each scenario, a single decision alternative was selected from these four possible decision alternatives: full backward integration, taper integration, partial integration and no integration.